2007
DOI: 10.1139/z07-034
|View full text |Cite
|
Sign up to set email alerts
|

Importance of diel behaviour when studying habitat selection: examples from female Scandinavian brown bears (Ursus arctos)

Abstract: The goal of habitat selection studies is to identify important habitats for a particular species. However, most studies using radiotelemetry have focused on habitat-selection patterns using daytime positions only. We used 24 h data from six female brown bears (Ursus arctos L., 1758) equipped with GPS-GSM collars and activity loggers to analyse variations in habitat selection related to diel variations in activity (foraging and resting). We found that the bears rested mainly during the daylight hours and forage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 26 publications
8
103
1
Order By: Relevance
“…the bimodal activity pattern displayed by Grizzly Bears in our study was similar to that reported for British Columbia (McCann 1991), Montana (Aune and Kasworm 1989*), and europe (Roth 1983;Roth and Huber 1986;Moe et al 2007), but the mid-day inactive period was longer and appeared to be the main rest period for the european bears. In contrast, male Grizzly Bears in Wyoming were active throughout the night and rested in mid-afternoon while females showed a pattern similar to our adult females (Holm et al 1999).…”
Section: Discussionsupporting
confidence: 90%
“…the bimodal activity pattern displayed by Grizzly Bears in our study was similar to that reported for British Columbia (McCann 1991), Montana (Aune and Kasworm 1989*), and europe (Roth 1983;Roth and Huber 1986;Moe et al 2007), but the mid-day inactive period was longer and appeared to be the main rest period for the european bears. In contrast, male Grizzly Bears in Wyoming were active throughout the night and rested in mid-afternoon while females showed a pattern similar to our adult females (Holm et al 1999).…”
Section: Discussionsupporting
confidence: 90%
“…Percentage of coniferous forest within a certain distance a Forest composition is an important determinant of brown bear habitat quality due to the high nutritional requirements of the species, its dependence on hard and soft mast during hyperphagia and the need for alternative food resources throughout the year (Preatoni et al 2005;Moe et al 2007). In the temperate zone, deciduous forests dominated by hard mast tree species are especially important for bears during hyperphagia (Fernández et al 2012) Deciduous In kilometers Human activities negatively affect brown bear habitat due to disturbance and persecution.…”
Section: Connectivity Analysismentioning
confidence: 99%
“…This assumption remains largely untested though, and it is unlikely that the same environmental factors determine both animal movements and habitat selection, and at the same scales (Roever et al 2014). This suggests that different input data, and potentially different modeling frameworks, should be used when modeling general habitat selection versus movement (Naves et al 2003;Moe et al 2007;Fernández et al 2012;Mateo Sánchez et al 2015a). Understanding how connectivity assessments are affected by relying on habitat models to define resistance surfaces is thus important for efficient corridor planning (Trainor et al 2013;Elliot et al 2014;Roever et al 2014;Mateo Sánchez et al 2015a, b).…”
Section: Introductionmentioning
confidence: 99%
“…One problem with this technique is the inability to detect fine-scale demographic or temporal influences on the relationship between habitat use and resources. Several studies, including some on swamp wallabies and other medium-sized macropods, have found important effects of demography and time of day on patterns of habitat use (Ager et al, 2003;Beyer and Haufler, 1994;Di Stefano et al, 2009;le Mar and McArthur, 2005;Moe et al, 2007;Swan et al, 2008). As such, analyses based on faecal pellet data provide information about broad patterns of habitat use that may hide important demographic or temporal effects.…”
Section: Relationships Between Relative Density and Resourcesmentioning
confidence: 99%